A human IgG-like bispecific antibody co-targeting epidermal growth factor receptor and the vascular endothelial growth factor receptor 2 for enhanced antitumor activity. Issue 2 (1st February 2016) - Chen, Zhiguo; Xie, Wei; Acheampong, Desmond Omane; Xu, Menghuai; He, Hua; Yang, Mengqi; Li, Chenchen; Luo, Chen; Wang, Min; Zhang, Juan
ABSRTRACT: Both Epidermal Growth Factor Receptor (EGFR) and the Vascular Endothelial Growth Factor Receptor 2 (VEGFR2) play critical roles in tumorigenesis. We hypothesized co-targeting EGFR and VEGFR2 using a bispecific antibody might have significant therapeutic potential. Here, we designed and produced a human IgG-like bispecific antibody (Bi-Ab) based on the variable regions of cetuximab (an anti-EGFR antibody) and mAb-04 (an anti-VEGFR2 antibody developed in our lab) . The Bi-Ab was found to inhibit the proliferation, survival and invasion of cancer cells via ablating phosphorylation of receptor and downstream signaling. In vivo efficacy was demonstrated against established HT-29 and SKOV-3 xenografts grown in nude mice. Studies revealed our Bi-Ab was able to restrain xenografted tumor growth and prolong survival of mice through inhibiting cell proliferation, promoting apoptosis and anti-angiogenesis. In contrast to cetuximab or mAb-04 alone, our Bi-Ab exhibits enhanced antitumor activity and has equal or slightly superior activity to their combination (Combi). It shows promise as a therapeutic agent, especially for use against tumors EGFR and/or VEGFR2 over-expressing malignancies.